2015
DOI: 10.4103/1673-5374.152383
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurogenesis in adult rats after ischemic brain injury: most new neurons fail to mature

Abstract: The present study examines the hypothesis that endogenous neural progenitor cells isolated from the neocortex of ischemic brain can differentiate into neurons or glial cells and contribute to neural regeneration. We performed middle cerebral artery occlusion to establish a model of cerebral ischemia/reperfusion injury in adult rats. Immunohistochemical staining of the cortex 1, 3, 7, 14 or 28 days after injury revealed that neural progenitor cells double-positive for nestin and sox-2 appeared in the injured co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Our results indicate that cells that proliferate during the first week after ischemia (cells labeled at post-stroke days 1–7), despite successfully differentiating into neuroblasts and reaching the ischemic cortex, are not able to survive long term. This may be because the number of cells that proliferate at this time is lower and/or due to the ischemic environment at that time, still hostile due to the inflammatory processes activated after brain damage, impeding the integration process 41 . Although the possible direct functional benefit of this limited neurogenesis is doubtful, it is possible that these neuroblasts that reach the injured area contribute to the functional recovery through the contribution of trophic factors and/or other substances that help the remaining cells to solve the conflict in which they are.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that cells that proliferate during the first week after ischemia (cells labeled at post-stroke days 1–7), despite successfully differentiating into neuroblasts and reaching the ischemic cortex, are not able to survive long term. This may be because the number of cells that proliferate at this time is lower and/or due to the ischemic environment at that time, still hostile due to the inflammatory processes activated after brain damage, impeding the integration process 41 . Although the possible direct functional benefit of this limited neurogenesis is doubtful, it is possible that these neuroblasts that reach the injured area contribute to the functional recovery through the contribution of trophic factors and/or other substances that help the remaining cells to solve the conflict in which they are.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of adult neurogenesis in response to many CNS trauma and neurological diseases has been reported by several studies in the past decade [ 184 , 185 ]. It has been demonstrated that ischemia is a well-known factor to contribute to reactive neurogenesis in the cortex [ 147 , 148 , 186 , 187 ]. The abnormal cortical neurogenesis has also been reported in multiple sclerosis [ 188 ] and ALS [ 189 ].…”
Section: Supportive Role Of Antioxidants In Promoting and Regulatimentioning
confidence: 99%
“…These neural stem/progenitor cells have the potential to survive brain ischemia and participate in neurogenesis after stroke [ 7 ]. The number of nestin-immunopositive cells (nestin + cells) is known to increase in the ischemic brain in response to focal cerebral ischemia/reperfusion injury [ 8 , 9 ]. However, while the effects of MH upon nestin + cells have been studied in neonatal cerebral hypoxic ischemic injury [ 10 - 13 ], as well as in adult global cerebral ischemia/reperfusion injury, which represents the clinical scenario of cardiac arrest [ 14 - 16 ], results have proved to be controversial and inconsistent.…”
Section: Introductionmentioning
confidence: 99%